The AMPK-mTOR Pathway Is Inhibited by Chaihu Shugan Powder, Which Relieves Nonalcoholic Steatohepatitis by Suppressing Autophagic Ferroptosis - Zheng Liang; Dajin Pi; Jianwei Zhen; Haizhen Yan; Chuiyang Zheng; July Liang Chen; Wen Fan; Qingliang Song; Jinyue Pan; Dongdong Liu; Maoxing Pan; Qinhe Yang; et al. (Hindawi Limited, 2024)
Nonalcoholic steatohepatitis (NASH) is the advanced stage of nonalcoholic fatty liver disease (NAFLD), which is distinguished by the accumulation of fat in the liver, damage to liver cells, and inflammation. Chaihu Shugan powder (CSP), a renowned traditional Chinese medicine (TCM) blend extensively utilized in China to address liver disease, has demonstrated its efficacy in reducing lipid buildup and effectively combating inflammation. Hence, the primary objective of this research is to examine the impacts and possible mechanisms of CSP on NASH through assessments of liver histopathology, lipidomic analysis, and gene expression. To induce a mouse model of NASH, we employed a diet which deficient in methionine and choline, known as methionine-choline deficient (MCD) diet. Initially, we examined the impact of administering CSP to NASH mice by assessing the levels of serum and liver indicators. We found that CSP was able to reduce lipid buildup and inflammation in mice. In addition, a total of 1009 genes exhibited enrichment in both the autophagy and ferroptosis pathways. The liver protein levels of Adenosine monophosphate-activated protein kinase-mammalian target of rapamycin (AMPK-mTOR)-mediated autophagy and ferroptosis markers, such as p-AMPKα/AMPKα, p-mTOR/mTOR, Beclin-1, microtubule associated protein 1 light chain 3 gamma (LC3), p62 (sequestosome 1 [SQSTM1/p62]), Kelch-like ECH-associated protein 1 (KEAP1), nuclear factor erythroid 2-related factor 2 (Nrf-2), ferritin heavy chain 1 (FTH1), and glutathione peroxidase 4 (GPX4), were restored by CSP. Furthermore, our findings indicated that the suppression of autophagy had a repressive impact on the occurrence of ferroptosis in the mouse model, indicating that autophagy activation likely plays a role in mediating ferroptosis in NASH.